Analisis Perbandingan Customer Experience dan Harga Pada Coffee Shop “Kopi Kenangan”, "Janji Jiwa" dan “Starbucks” Di Cikarang - Nurul Hidayah; Arum Nur F; Wita Supira; Elyza Fauziah; Sri Ratna S; Yani Fuzi A; Melati Sabrina K; Nazwa Ramadhita; Muhammad Rifki; Muhammad Haidar A; Sihotang Martin C; Miftakul Huda (Journal of Management and Creative Business, 2024)
Enjoying coffee in a coffee shop is a pretty comfortable thing. It's already become a lifestyle in the community. It's this kind of lifestyle that makes the coffee shop grow more and more. In addition to this lifestyle, the consumption of coffee products in a coffee shop grows and the tendency to enjoy coffee in a coffee shop becomes natural. The purpose of this study is to test and analyze the differences in customer experience and prices on coffee shop Starbucks, Kopi Kenangan, Janji Jiwa in Cikarang Baru. The population used in this research is customers Starbucks, Kopi Kenangan, Janji Jiwa di Cikarang Baru. The sample in this study was based on the experimental sample so it was obtained by as many as 50 respondents. The method of analysis used is the kuntitative method with a comparative descriptive approach and USES validity tests, immobility tests, normality tests, and anova comparisons. Research shows that there are no discrepancy in the custumer experience and prices on Coffee Shop Starbucks, Kopi Kenangan, Janji Jiwa in Cikarang Baru.